Źródła nacjonalizmu czerkieskiego i jego konsekwencje polityczne - Bodio, Tadeusz; Sieradzan, Przemysław J. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The problem of the increasing threat to Russian security in the area of the Northern Caucasus is described as originating in the ethnic groups from the mountainous region located between the Caspian, Black and Azov Seas. The hundreds of ethnic and sub-ethnic groups living there have their own identities and are aware of their individuality. This makes the Northern Caucasus the most unstable of all regions in the Russian Federation. One of the more serious threats to the national security and territorial integrity of the Russian state is posed by separatist movements in the Northern Caucasus. Caucasian enthnoses and elites have various levels of national consciousness, political ambitions and loyalties towards Moscow. The ethnic situation in north-west Caucasus is becoming increasingly tense, and the organizations of Circassian autonomists and separatists are winning more and more support. A lot seems to suggest that as the date of the Winter Olympic Games in Sochi draws nearer the protests of the Adigeian population are likely to escalate, both in the Russian Federation and abroad. The ‘Circassian issue’ is a significant ethno-political challenge faced by the authorities of the Russian Federation.